Pectin‐based pellets for crayfish aquaculture: structural and functional characteristics and effects on redclaw Cherax quadricarinatus performances. (10th October 2014) - Volpe, M.G.; Santagata, G.; Coccia, E.; Di Stasio, M.; Malinconico, M.; Paolucci, M.
Abstract: Pectin is a promising candidate to be employed as binder for manufacturing pellets for crayfish feeding. In this study, the gelling properties of different types of pectin and their effects on Cherax quadricarinatus performances have been analysed. Pectins with different degree of esterification from apple and citrus were screened to select those with the best gelling properties to be employed in pellet manufacturing. Three pectins were selected: low esterification degree apple pectin (LEAP), low esterification citrus pectin (LECP) and high esterification degree apple pectin (HEAP). Scanning electron microscopy analysis, nutrient leaching and water uptake indicated that LEAP showed the best aggregating properties, followed by LECP and HEAP pellets. Cherax quadricarinatus performances were affected by the pectin type, with redclaw fed LEAP pellets showing the highest ( P < 0.05) growth rate and amylase activity ( P < 0.05) in the gastrointestinal tract. Altogether these results indicate that LEAP can be considered an excellent binder for feed pellets due to its gelling properties and its efficacy to improve growth and stimulation of digestive enzyme activity.